The Relationship Between the Frequency of Prenatal Exercise and Edema in Third Trimester Pregnant Women at Benoa Public Health Center - Anis Rahmawati; Retno Dewi Prisusanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Edema is a common physiological complaint experienced by pregnant women, particularly during the third trimester, which may affect maternal comfort and daily activities. Prenatal exercise is considered a safe, non-pharmacological intervention that can improve maternal circulation and reduce fluid retention. This study aimed to analyze the relationship between the frequency of prenatal exercise and the incidence of edema in third trimester pregnant women in the working area of Benoa Public Health Center. A cross-sectional analytical design was employed, involving 30 pregnant women selected using purposive sampling. Data were collected through structured questionnaires and physical examination to assess the presence of edema, while the frequency of prenatal exercise was categorized into regular (≥3 sessions per week) and irregular (<3 sessions per week). Descriptive statistics summarized participant characteristics, and the Chi-square test was used to evaluate the association between prenatal exercise frequency and edema, with a significance level of p < 0.05. The results indicated that 26.7% of women who exercised regularly experienced edema, compared to 66.7% of those who exercised irregularly. Statistical analysis confirmed a significant relationship between exercise frequency and edema occurrence (χ² = 5.33, p = 0.021). These findings suggest that consistent participation in prenatal exercise is associated with a lower incidence of edema among third trimester pregnant women. Integrating structured exercise programs into routine antenatal care is recommended to enhance maternal well-being, prevent pregnancy-related discomforts, and support overall health during late pregnancy.